Perancangan Alat Vakum untuk Meningkatkan Daya Tahan Produk Olahan Ikan Gabus di PT. XYZ - Brilliant Mahardika Wah Martus Putra; Iwan Nugraha Gusniar; Bobie Suhendra (Jurnal Serambi Engineering, 2024)
The fisheries goods known as processed snakehead fish products are susceptible to spoilage when stored for extended periods of time. Using a vacuum sealer during the packing process is one way to prevent processed snakehead fish items from spoiling. As a result, we will be designing a vacuum machine in this research. The goal of the Vacuum Machine's design and packaging is to increase the processed snakehead fish product's selling value while also prolonging its useful life. It is anticipated that the machine under design would be capable of packing tasks that can be finished quickly and affordably. There are several pieces to this machine, such as the vacuum motor, and vacuum clamp.